2022
DOI: 10.3389/fonc.2022.930220
|View full text |Cite
|
Sign up to set email alerts
|

FBXO9 Mediates the Cancer-Promoting Effects of ZNF143 by Degrading FBXW7 and Facilitates Drug Resistance in Hepatocellular Carcinoma

Abstract: F-box proteins are critical for malignancy because they control the turnover of key proteins that govern multiple cellular processes. F-box protein 9 (FBXO9) belongs to the F-box protein family and exhibits oncogenic properties in hematological malignancies. However, the function and molecular mechanism of FBXO9 in hepatocellular carcinoma (HCC) remain unclear. Here, we report that FBXO9 was remarkably overexpressed in HCC. Loss- and gain-of-function experiments showed that FBXO9 facilitates HCC cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Interestingly, in line with this finding, it has been reported that increased UBD levels in rectal cancer correspond to favorable treatment outcomes [49]. On the contrary, FBXO9 has been implicated in driving drug resistance in hepatocellular carcinoma [50]. This inconsistency is likely due to different cancer types, as FBXO9 was found to overexpress in hepatocellular carcinoma [50].…”
Section: Potential Mechanisms Underlying Ubiquitination-mediated Ov Riskmentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, in line with this finding, it has been reported that increased UBD levels in rectal cancer correspond to favorable treatment outcomes [49]. On the contrary, FBXO9 has been implicated in driving drug resistance in hepatocellular carcinoma [50]. This inconsistency is likely due to different cancer types, as FBXO9 was found to overexpress in hepatocellular carcinoma [50].…”
Section: Potential Mechanisms Underlying Ubiquitination-mediated Ov Riskmentioning
confidence: 64%
“…On the contrary, FBXO9 has been implicated in driving drug resistance in hepatocellular carcinoma [50]. This inconsistency is likely due to different cancer types, as FBXO9 was found to overexpress in hepatocellular carcinoma [50]. Therefore, it is reasonable to deduce that the activity of ubiquitination, marked by FBXO9 and UBD expression, enhances the responsiveness to a range of drugs.…”
Section: Potential Mechanisms Underlying Ubiquitination-mediated Ov Riskmentioning
confidence: 99%
“…In addition, magnolol reverses degradation and ubiquitination levels of PPARγ conferred by FBXO9, suggesting that magnolol stabilizes PPARγ by interrupting the interaction of PPARγ and FBXO9. FBXO9, a member of the F-box protein family and a substrate recognition component of the S-phase kinase associated protein 1 (Skp1)-cullin-1-F-box (SCF) E3 ligase complex, has been reported to participate in several cellular processes [37][38][39]. FBXO9 plays a pivotal role in the proteasome-dependent degradation of its substrates, including F-box/WD repeat-containing protein 7 (FBXW7) [38], cellular tumor antigen p53 [39], and PPARγ [15].…”
Section: Discussionmentioning
confidence: 99%
“…FBXO9, a member of the F-box protein family and a substrate recognition component of the S-phase kinase associated protein 1 (Skp1)-cullin-1-F-box (SCF) E3 ligase complex, has been reported to participate in several cellular processes [37][38][39]. FBXO9 plays a pivotal role in the proteasome-dependent degradation of its substrates, including F-box/WD repeat-containing protein 7 (FBXW7) [38], cellular tumor antigen p53 [39], and PPARγ [15]. Lee et al identified FBXO9 as a repressor of adipogenesis in 3T3-L1 preadipocytes by destabilizing PPARγ [15].…”
Section: Discussionmentioning
confidence: 99%
“…FBXO9 (also known as FBX9 or NY-REN-57) belongs to the FBXO subfamily and is recognized as the substrate recognition subunit of the CRL1/SCF E3 ligase complex [ 33 ]. FBXO9 tends to exhibit oncogenic behavior in conditions such as multiple myeloma and hepatic carcinoma [ 34 , 35 ], although its role in various diseases (including cancer) is largely overlooked. However, it inhibits tumorigenesis in acute myeloid leukemia [ 36 ].…”
Section: Introductionmentioning
confidence: 99%